‘A Church for the Poor’: High- Church Slum Ministry in Anderston, Glasgow, 1845–51 - Strong, Rowan (The journal of ecclesiastical history, 1999)
In December 1845 Bishop Michael Russell of Glasgow and Galloway wrote to a keen young Episcopalian layman, Alexander James Donald D'Orsey, a teacher at the High School in Glasgow, suggesting ordination. Conscious of the growing numbers of immigrant Episcopalians in the western suburbs of Glasgow, the bishop's intention was to stimulate a new congregation for ‘the wants of the poorer class there’. Evidently D'Orsey was already known to the bishop for he mentions him as pleading ‘with your usual eloquence’ the cause of the Episcopalian Church Society, which would raise part of the £80 stipend. Russell envisaged that D'Orsey would work in this new congregation for a year or two until something more worthy of the young man's talents came up. D'Orsey wrote stating that the proposal was attractive, not least because it was a congregation which would primarily be comprised of the ‘humbler classes’. He would continue in his present work and undertake the congregational duties part-time. His present income made it preferable to refuse the stipend, suggesting that it should go to augment the livings of poorer clergy. As a new priest D'Orsey went on to create the congregation that eventually became St John's, Anderston, and to become embroiled with Russell's successor, Bishop Walter Trower, over ritualism in the parish. The deposit of D'Orsey's correspondence with these two bishops in the National Library of Scotland provides the opportunity for a localised insight into the emergence of Episcopalian ministry to the poor in nineteenth-century Scotland's most industrialised city, and to the connection of such ministry with ritualism.